Structure-Activity Relationships and Transcriptomic Analysis of Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibitors - Andrey A. Poloznikov; Sergey V. Nikulin; Dmitry M. Hushpulian; Anna Yu. Khristichenko; Andrey I. Osipyants; Andrey F. Asachenko; Olga V. Shurupova; Svyatoslav S. Savin; Sue H. Lee; Irina N. Gaisina; Gregory R. J. Thatcher; Anthony Narciso; et al. (MDPI AG, 2022)
To evaluate the differences in action of commercially available 2-oxoglutarate mimetics and "branched-tail" oxyquinoline inhibitors of hypoxia-inducible factor prolyl hydroxylase (HIF PHD), the inhibitors' IC50 values in the activation of HIF1 ODD-luciferase reporter were selected for comparative transcriptomics. Structure-activity relationship and computer modeling for the oxyquinoline series of inhibitors led to the identification of novel inhibitors, which were an order of magnitude more active in the reporter assay than roxadustat and vadadustat. Unexpectedly, 2-methyl-substitution in the oxyquinoline core of the best HIF PHD inhibitor was found to be active in the reporter assay and almost equally effective in the pretreatment paradigm of the oxygen-glucose deprivation in vitro model. Comparative transcriptomic analysis of the signaling pathways induced by HIF PHD inhibitors showed high potency of the two novel oxyquinoline inhibitors (#4896-3249 and #5704-0720) at 2 μM concentrations matching the effect of 30 μM roxadustat and 500 μM dimethyl oxalyl glycine in inducing HIF1 and HIF2-linked pathways. The two oxyquinoline inhibitors exerted the same activation of HIF-triggered glycolytic pathways but opposite effects on signaling pathways linked to alternative substrates of HIF PHD 1 and 3, such as p53, NF-κB, and ATF4. This finding can be interpreted as the specificity of the 2-methyl-substitute variant for HIF PHD2.